Serum Progesterone profile of pregnant Ettawa crossbred does at day-0, -21, -42, -63 and -84 - Bellani, Ayu Aprodhita Cintya; Ismudiono, Ismudiono; Hariadi, Mas'ud; Lokapirnasari, Widya Paramita (Universitas Airlangga, 2021)
This study aimed to determine the progesterone concentrations of Ettawa crossbred does at day-0, -21, -42, -63, and -84 after mating. Five Ettawa crossbred does were injected with PGF2α twice with an interval of 11 days for estrous synchronization followed by natural mating on day-3 after the second PGF2α injection. Blood was collected through the jugular vein for the measurement of serum progesterone concentrations using ELISA, whereas pregnancy was diagnosed at 90 days after mating by abdominal palpation. The results showed that all does were on estrus onthethird day after the second PGF2α, three of them diagnosed to be pregnant following mating. The progesterone concentration at day-0 was 1.52 ± 0.33 ng/mL, increased (p <0.05) to 7.08 ± 1.02 and 5.50 ± 2.82 ng/mL at day-21 and day-42, and increased (p <0.05) again to 12.01 ± 5.30 and 12.04 ± 0.30 ng/mL at day 63 and day 84, respectively. There was no significant difference in progesterone concentrations between day 21 and day 42 and between day 63 and day 84. It could be concluded that there was a biphasic increase of progesterone concentrations of the pregnant Ettawa crossbred does, i.e. from day-0 to day-21/day-42 and from day-21/day-42 to day-63/day-84.